Improving student’s mathematical problem solving skills through Quizizz - Setiyani, Setiyani; Fitriyani, Nur; Sagita, Laela (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2020)
The Industrial Revolution 4.0 on Education in Indonesia affects school activities rapidly. Teachers are no longer educated in classrooms only, but they can also utilize technology to conduct distance learning. One interactive application that can be used as a form of question exercise is Quizizz. Therefore, this research aims to: first, examine the effectiveness of students' activities by using Quizizz on mathematical problem-solving skills; second, investigate the differences in the increase in students' ability to solve mathematical problems between the class with and without the Quizizz-aided learning method; third, describe the activities of students who used the Quizizz-aided drill learning method; and fourth, describe the students' responses in using Quizizz. The research was quasi-experiment with a pretest-posttest non-equivalent control group design. The participants in this study are 67 of 10th students divided into experimental and control classes. Data collection techniques used were tests for students' mathematical problem-solving skills and questionnaires. The instruments were validated using Pearson correlation, while the reliability was tested using Cronbach's Alpha. Then, the N-gain test was used to analyze the data. The results showed that there was an effect on students’ learning activities by using Quizizz on their problem-solving skills. Besides, there was a difference in the improvement of problem-solving skills between the class with and without Quizizz-aided. Furthermore, students’ activities in three meetings have increased. Moreover, students provided a positive response in learning using Quizizz. Thus, it can be concluded that Quizizz is effective in improving mathematical problem-solving skills.